Challenges of mine closure as a tool for reconciling mining with local communities and conservation units in the Amazon - Evangelista Kutchenski Junior, F; Perlatti, F; Marques, AE; Carneiro de Jesus Neto, J (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
The Amazon is a beautiful region renowned for its vast biodiversity and mineral wealth. Notably, it hosts the world's largest iron mine, which not only generates thousands of jobs and local income but also drives the regional economy. However, it is crucial to emphasise that the exploitation of these resources must be balanced with environmental conservation and respect for the indigenous communities inhabiting the area. Unfortunately, illegal mining activities pose a significant threat to the Amazon, causing irreparable damage to the environment and directly affecting local communities. It is essential to combat this harmful practice and promote a sustainable mining model that prioritises people's wellbeing and ecosystem preservation. In this context, mine closure in the Amazon region emerges as a crucial tool to mitigate the environmental impacts of mining activities. Adopting progressive closure practices not only reduces the impact during operation but also contributes to the conservation of mineral resources, preventing disorderly land occupation and the unchecked expansion of agriculture and livestock farming. It is fundamental to recognise that when conducted responsibly and sustainably, mining in the Amazon can be an ally in conserving mineral resources. Therefore, it is imperative to promote policies and practices that ensure an integrated and balanced approach between economic development and environmental preservation in the region. This paper presents an analysis of data regarding mining activities around significant conservation units, local communities, and indigenous territories, with a focus on the main existing conflicts.
Keywords: Amazon; mining; mine closure; environmental conservation; local communities; indigenous territories